TINJAUAN TERHADAP PENETAPAN PERKARA NOMOR 5408/Pdt.G/2018/PA.Cbn. TENTANG NAFKAH IDDAH BAGI ISTERI YANG DICERAI TALAK KARENA NUSYUZ DI PENGADILAN AGAMA CIBINONG - Farida Syafar, Hasna (Aksara Public, 2019)
This thesis aims to determine the consideration of the Cibinong Religious Court judges about divorce divorce decisions that determine the living allowance for the wife of nusyuz in case Number 5408 / Pdt, G / 2018 / Pa.Cbn, and the position of the iddah for nusyuz wives and the legal implications from the provision of the living iddah. This study shows that the wife who has divorced from her husband with raj'i divorce then still gets the rights from her ex-husband, which is called the iddah income for the duration of her iddah. However, the wife who did the nusyuz and the husband divorced her then her right to live was killed. As in Article 80 paragraph 7 of the Compilation of Islamic Law (KHI), which reads the Obligation of the husband as referred to in paragraph (5), the wife of nusyuz and article 152 reads: The ex-wife has the right to get a living from her ex-husband, except if he forgets. But not all cases caused by Nusyuz's deceased wife get a living, if in the trial the husband is voluntary and is able to provide a living for his ex-wife.